IDEAL SOLUTIONS FOR RAILWAY SQUATTING IN MALAYSIA: ALTERNATIVES TO EVICTION - Najah Inani Abdul Jalil; Khuzaimah Mat Salleh (Journal of Islamic, Social, Economics and Development, 2018)
The provision of affordable housing in Malaysia has become a major problem for the policymaker. The problems are reflected by the mushrooming of squatters especially on railway land. The purpose of this research is to propose for alternatives solutions to railway squatters as compared to prevalent eviction procedures taken by the authorities. The solution for the eradication of railway squatters must be uniquely designed as eviction shall not be considered as a prototype in eradicating the railway squatters. The problems associated with eviction are violence to occupants, properties and in most cases, there are high possibilities of re-entry incidence by the squatters into a new illegal settlement. Hence, it is important to find alternatives solution which enable to provide some insight on how the problems to be solved holistically. In doing so, the research is executed by the analysis on the statutory provisions, decided cases and articles with the discussion on squatter’s resettlement programme from foreign countries with the belief that the myriad of solutions may be expensive but most of the failed resettlement programme resulted from the one-size-fit-all type of solutions. The research will discuss on the practice from the foreign countries as solutions for the squatter’s resettlement.